Alginate–hyaluronan composite hydrogels accelerate wound healing process. (20th October 2015) - Catanzano, O.; D'Esposito, V.; Acierno, S.; Ambrosio, M.R.; De Caro, C.; Avagliano, C.; Russo, P.; Russo, R.; Miro, A.; Ungaro, F.; Calignano, A.; Formisano, P.; et al.
Highlights: Alginate/Hyaluronan composite hydrogels for wound dressing are proposed. Hyaluronan at different concentrations does not interfere with internal gelation process. Hyaluronan-containing hydrogels promote healing in Ad-MSC or HaCaT cell cultures as well as in a rat model of excised wound. Alginate/Hyaluronan biofunctional hydrogels turn to be a versatile platform to translate in a clinical setting. Abstract: In this paper we propose polysaccharide hydrogels combining alginate (ALG) and hyaluronan (HA) as biofunctional platform for dermal wound repair. Hydrogels produced by internal gelation were homogeneous and easy to handle. Rheological evaluation of gelation kinetics of ALG/HA mixtures at different ratios allowed understanding the HA effect on ALG cross-linking process. Disk-shaped hydrogels, at different ALG/HA ratio, were characterized for morphology, homogeneity and mechanical properties. Results suggest that, although the presence of HA does significantly slow down gelation kinetics, the concentration of cross-links reached at the end of gelation is scarcely affected. The in vitro activity of ALG/HA dressings was tested on adipose derived multipotent adult stem cells (Ad-MSC) and an immortalized keratinocyte cell line (HaCaT). Hydrogels did not interfere with cell viability in both cells lines, but significantly promoted gap closure in a scratch assay at early (1 day) and late (5 days) stages as compared to hydrogels made of ALG alone ( p < 0.01 and 0.001 for Ad-MSC and HaCaT, respectively). In vivo wound healing studies, conducted on a rat model of excised wound indicated that after 5 days ALG/HA hydrogels significantly promoted wound closure as compared to ALG ones ( p < 0.001). Overall results demonstrate that the integration of HA in a physically cross-linked ALG hydrogel can be a versatile strategy to promote wound healing that can be easily translated in a clinical setting.